Sekuralisme Politik dan Fundamentalisme Agama: Ketegangan Kreatif Hubunan Agama dan Politik - Nashir, Haedar (Unisia, 2016)
The discourse on the secularization of politics and the fundamentalism of religion constitutes an interesting theme and includes the complex problem. The secularization of politics as a rigid form of rigid secularism or an extreme secularization isolates religion from state is not only a single phenomenon but it also relation with the trend of religion understanding. It covers response to abuse of state management, especially about the theocratic system and the institutionalization of religion in naive politic. But at the same time the secularization of politics beside causes and refuses the religion involving, and it also cannot answer demoralization of political state as whole, so it appears the fundamentalism of religion rigidly. In this respect, it needs new alternative to find a relationship model between religion and political domain that more flexible, dynamic, it is toward modifying prophetical politic.